Heterogeneously Catalysed Oxidative Dehydrogenation of Menthol in a Fixed‐Bed Reactor in the Gas Phase. Issue 8 (11th June 2019) - Kulik, Anna; Neubauer, Katja; Eckelt, Reinhard; Bartling, Stephan; Panten, Johannes; Köckritz, Angela
Abstract: For the first time, the oxidative dehydrogenation of (−)‐menthol to (−)‐menthone and (+)‐isomenthone in a marketable quality was carried out in a continuous gas phase reactor as a sustainable process using molecular oxygen as green oxidant and solid catalysts which do not contaminate the product mixture and which are easily to remove. The diastereomeric purity remained largely unchanged. Three types of catalysts were found to be very active and selective in the formation of menthone and isomenthone: AgSr/SiO2, CuO distributed on a basic support and RuMnCe/CeO2, where Ru, Mn and Ce exist in an oxidized state. The best overall yield of menthon/isomenthone obtained with an Ag‐based catalyst was 58 % at 64 % selectivity, with a Cu‐based catalyst 41 % at 51 % selectivity and with a Ru‐based catalyst 68 % at 73 % selectivity. Reaction conditions were widely optimized. Abstract : Catalysis in the gas phase for fine chemicals : For the first time, a continuous process using heterogeneous Ag‐, Cu‐ and Ru‐based heterogeneous catalysts was developed for the synthesis of (−)‐menthone and (+)‐isomenthone from (−)‐menthol. A total yield of 68 % at 73 % selectivity was obtained using Ru as active species.